Role of Silicon and Salicylic Acid in the Mitigation of Nitrogen Deficiency Stress in Rice Plants - Deus, Angelica Cristina Fernandes [UNESP]; Prado, Renato de Mello [UNESP]; Alvarez, Rita de Cassia Felix; Oliveira, Raimundo Leonardo Lima de [UNESP]; Felisberto, Guilherme [UNESP] (Springer, 2020)
Application of silicon (Si) and salicylic acid (SA) mitigates plant stress; however, this effect is not known under nitrogen (N) deficiency conditions in rice plants. The objective of the present study was to determine whether foliar application with a soluble form of Si and SA, individually or in combination, could mitigate N deficiency stress in rice plants. The treatments consisted of application of 3.45 g L-1 Si only (sprayed on the leaves), 4.5 mM SA only, a combination of both, and no application as control. Net CO2 assimilation rate, transpiration, lignin and carbon contents, C:N:P:Si stoichiometric ratio and grain yield were evaluated. Foliar application of Si combined with SA or isolated application of SA did not mitigate N deficiency stress in rice plants. However, silicon application increased rice yield by 18.6% in N-deficient conditions. Our results show that the beneficial effects of Si under nitrogen deficient conditions are related to the stoichiometry change in C with Si and increases of lignin synthesis.
Keywords: Carbon; Beneficial element; Foliar application; Lignin; Nutritional deficiency; Oryza sativa